ANALISIS HASIL BELAJAR SISWA KELAS X BERDASARKAN NILAI UN DAN PILIHAN PSB ONLINE SMK NEGERI 5 PADANG - 327-331 , Putri Ayu Dwiyana (CIVED, 2014)
ABSTRACT   This study aimed to analyze student learning outcomes based on the value of the UN and the PSB online selection of class X in SMK Negeri 5 Padang Academic Year 2012/2013. Type of research is comparative and correlational research. Sampling technique that is proportional random sampling with a sample of 224 students. Based on the results of different test data analysis with One Way ANOVA significance value 0.766> 0.05, then there is no difference in the value of the learning outcomes of students who pass option 1, 2 and 3 of each course. In correlation with Product Moment analysis shows generate significant value 0.611> 0.05 alpha so there is no relationship between the value of the UN with the learning outcomes of students of class X of SMK Negeri 5 Padang Academic Year 2012/2013. Keywords : PSB Online , Value UN , Learning Outcomes